Zavedanje in izvajanje ukrepov za spoštovanje človekovih pravic v gospodarstvu - Čertanec, Ana (Podjetje in delo, 2025)
Business enterprises are increasingly aware that respecting human rights is no longer a matter of choice, but a requirement arising from legislation, international standards, and social pressure. This paper analyses the level of awareness and the implementation of measures aimed at respecting human rights in Slovenia. As a result of voluntary commitments, in recent years, enterprises have begun to adopt human rights policies and due diligence procedures in an effort to reduce the gap between declaratory recognition of the importance of human rights and their actual implementation. Despite these developments, the analysis reveals significant gaps-particularly in the areas of systematic risk assessment, stakeholder engagement, integration of human rights into business strategies, and the establishment of effective grievance mechanisms. Methodologically, the paper is based on a comparative analysis with international standards, in particular the United Nations Guiding Principles on Business and Human Rights, and incorporates insights from foreign research. The findings show that business enterprises still tend to treat respect for human rights primarily as an administrative obligation rather than a strategic objective. The paper therefore emphasizes that voluntary commitments are insufficient and calls for a systemic and legally supported regulatory framework.
Keywords: business; človekove pravice; due diligence; human rights; human rights and business; podjetja; skrbni pregled; Slovenia; Slovenija; Smernice OZN; spoštovanje človekovih pravic v gospodarstvu; sustainability; trajnostnost; UN Guiding Principles